Korelasi Kemandirian Belajar dan Motivasi Belajar dengan Hasil Belajar Peserta Didik dalam Pembelajaran IPAS di Kelas IV SDN 06 Pontianak Selatan: Penelitian - Merry Wulan Agustin; Kartono; Asmayani Salimi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to describe the level of correlation between learning independence and learning motivation with the learning outcomes of fourth-grade students of State Elementary School 06 South Pontianak. The method used in this study is a descriptive method with a correlation study research form. The population in this study were fourth-grade students of State Elementary School 06 South Pontianak. Sampling used a simple random sampling technique with a sample size of 32 students. Data collection techniques used in this study were indirect communication techniques and documentary studies. Indirect communication techniques were used to collect data on learning independence and student learning motivation with a questionnaire while documentary study techniques were used to collect data on learning outcomes of fourth-grade students of State Elementary School 06 South Pontianak. The data analysis technique used with statistical analysis showed an average of student learning independence of 84.31, an average of learning motivation of 81.09 and an average of learning outcomes of 83.88. Statistical calculations using the product moment correlation formula, namely learning independence with learning outcomes obtained 0.674, learning motivation with learning outcomes obtained 0.605, and learning independence with learning motivation obtained 0.536, for learning independence and learning motivation with learning outcomes using the multiple correlation formula obtained R of 0.733 included in the category of strong relationships with Fcount 16.89 and ɑ = 5% of 3.33 which means (16.89) > (3.33), then Ha is accepted. So it can be concluded that there is a strong and positive relationship between learning independence and learning motivation with the learning outcomes of class IVB students of State Elementary School 06 South Pontianak.